2005
DOI: 10.1088/0022-3727/39/1/r01
|View full text |Cite
|
Sign up to set email alerts
|

New era of silicon technologies due to radical reaction based semiconductor manufacturing

Abstract: Current semiconductor technology, the so-called the molecule reaction based semiconductor manufacturing, now faces a very severe standstill due to the drastic increase of gate leakage currents and drain leakage currents. Radical reaction based semiconductor manufacturing has been developed to completely overcome the current standstill by introducing microwave excited high density plasma with very low electron temperatures and without accompanying charge-up damage.The introduction of radical reaction based semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
115
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 33 publications
0
115
0
Order By: Relevance
“…Regarding the plasma treatment, the SiH 4 plasma treatment was carried out on the GaN sample using the microwave excited high density plasma [20] during 30 seconds. Ar gas was used as the plasma excitation gas.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the plasma treatment, the SiH 4 plasma treatment was carried out on the GaN sample using the microwave excited high density plasma [20] during 30 seconds. Ar gas was used as the plasma excitation gas.…”
Section: Methodsmentioning
confidence: 99%
“…(3) An oxide film was prepared by the oxidation using oxygen radicals (hereafter referred as oxygen-radical oxidation) at 400°C. Here, oxygen radicals were produced in a microwave-excited high-density Kr(97%)/O 2 (3%) mixture plasma [10,11] oxidation all oxide films were kept in isopropyl alcohol solution, from which O 2 gas were removed completely, immediately after their preparation until their photoelectron spectra were measured. We measured the Si 2p spectra arising from the oxide films at the external photoelectron take-off angles (TOAs) of 10°, 15°, 20°, 30°, 52°, and 85°at the vacuum/SiO 2 interface.…”
Section: Methodsmentioning
confidence: 99%
“…In this experiment, we used microwaveexcited high-density plasma equipment [4] with process gasses of Kr/O 2 /NO and PECVD using microwave-excited high-density Kr/O 2 /SiH 4 plasma with dual shower plate [3,5] for formation of gate insulator films. After 5-step room temperature cleaning [6], gate insulator films were grown by three methods as follows (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that high temperature NO and N 2 O anneals are effective for reduction of interface trap density [2]. On the other hand, radical reactor based processes can form high quality gate insulator films on silicon surfaces at low temperature [3,4].…”
Section: Introductionmentioning
confidence: 99%